Participation and quality of life: a study on the people's empowerment in a Malay village community - Abu Samah, Asnarulkhadi (Universiti Putra Malaysia Press, 2006)
Empowerment is often said to take place when people collectively organise themselves to fight the rich, the powerful, the owner of large businesses and other forms of oppression. However, this has not always been the case. Community empowerment is also embedded in the people's participation when dealing with their everyday community life. It is within the process of how individuals take control over their life depicts the elements of community empowerment. This paper portrays the people empowerment through their participations in a Malay village community. It illustrates the people's awareness towards the emergent common needs and problems. People's consciousness is translated into a collective action when they organised themselves and participated in various group-based organisations. These self-propelling groups are avenues for members to offer assistance in order to meet the groups' goal. In this community-driven endeavour, individuals develop their capacity to affect change in their community life, enabling them to develop competence, learn to use collective effort to shape the outcomes that benefit them and ultimately, take control over their life. It is within this participation process that the people's empowerment is embraced and developed, enabling them to gradually improve their quality of life in the community environment.